Frontiers of time - Time-Life Books (Alexandria, Va. : Time-Life Books, 1991)
Examines the origins, evolution, and eventual fate of the universe.
Includes bibliographical references (p. 137-140) and index.
Wilson's Public Library.
7-10.
Young Adult
Keywords: Cosmology; Universe